2006
DOI: 10.1159/000095570
|View full text |Cite
|
Sign up to set email alerts
|

Can the Requirement of a Diversion Procedure Be Predicted after an Uncomplicated Intracranial Hydatid Cyst Surgery?

Abstract: Intracranial hydatidosis is mainly a pediatric disease. Surgical evacuation of the mass in toto is the gold standard of therapy. No concise data related to the requirement of diversion procedures after uncomplicated hydatid cyst removal is encountered in the literature. The aim of this report is to focus on this idea and estimate the necessity of a diversion procedure beforehand. A 6-year-old girl both with intracranial and renal involvement of hydatidosis underwent surgery. Intact removal of the intracranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…[3][4][5] Hydatid disease is endemic in cattle-and sheep-rearing regions of the world such as Central Europe, the Mediterranean countries, the Middle East, South America, Australia, New Zealand, and South Africa. [1] In India it is commonly seen in the Kurnool district of Andhra Pradesh, Madurai district of Tamil Nadu and in Punjab. [6,7] But this case hails from a non-endemic area in India i. e., Uttar Pradesh.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] Hydatid disease is endemic in cattle-and sheep-rearing regions of the world such as Central Europe, the Mediterranean countries, the Middle East, South America, Australia, New Zealand, and South Africa. [1] In India it is commonly seen in the Kurnool district of Andhra Pradesh, Madurai district of Tamil Nadu and in Punjab. [6,7] But this case hails from a non-endemic area in India i. e., Uttar Pradesh.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple cysts occurs due to embolisation from hydatid cyst located in the heart. [12] Onal et al [1] and Lunardi et al [15] reported occurrence of multiple cysts in their studies. The primary cysts are fertile as they contain scolices and brood capsules hence, rupture of primary cyst can result in recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with intracranial cysts usually present with focal neurological deficit and features of raised intracranial pressure; the latter may be due to the large size or due to interference with pathway of CSF flow [1]. Surgically intact cyst excision is the ideal treatment [2].…”
Section: Discussionmentioning
confidence: 99%
“…Due to slow growth of the cyst, patients usually present with a large cyst at the time of diagnosis. Typically, cysts initially manifest as focal neurologic deficits or symptoms related to increased intracranial pressure (5). The optimal management of intracranial hydatid cysts is intact surgical removal of the cyst.…”
Section: Introductionmentioning
confidence: 99%